Discrete Fractional Solutions of a Legendre Equation - Yilmazer, Resat (Amer Inst Physics, 2018)
One of the most popular research interests of science and engineering is the fractional calculus theory in recent times. Discrete fractional calculus has also an important position in fractional calculus. In this work, we acquire new discrete fractional solutions of the homogeneous and non homogeneous Legendre differential equation by using discrete fractional nabla operator.
6th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 15-17, 2017 -- Budapest, HUNGARY